S(E)2 reaction in noncarbon system: Metal-halide catalysis for dehydrogenation of ammonia borane - Pai, Sung Jin; Han, Sang Soo (NATL ACAD SCIENCES, 2017)
An electrophilic substitution (S-E) reaction of BN isosteres has been investigated for the dehydrogenation of ammonia borane (AB) by metal chlorides (MCl2) using various ab initio calculations. In contrast to the typical S-E reaction occurring at the carbon atom, the nitrogen atom in AB serves as the reaction center for the S-E reaction with the boron moiety as the leaving group when the MCl2 approaches the AB. The S(E)2 backside reaction is favored as a trigger step for the dehydrogenation of AB by the MCl2. The SE2 reaction is found for 3d-transition-metal chlorides (e.g., FeCl2, CoCl2, NiCl2, CuCl2, and ZnCl2), while PdCl2 leads to the dehydrogenation of AB by a direct B-H sigma-bond activation, similar to most organometallic catalysts. Interestingly, the polymerization of AB promoted by MCl2 can be explained with the similar S(E)2 mechanism, and the dehydrogenation of the BN derivative 3-methyl-1,2-BN-cyclopentane (CBN) bearing a carbon backbone ring also follows the S(E)2 reaction. In particular, the experimental observation that the use of metal-chloride catalysis decreases the by-products obtained during the hydrogenation of AB can be explained by our mechanism involving the S(E)2 reaction. This work is helpful for the development of novel metal-halide catalysts for practical hydrogen storage materials, including the BN moiety.
Keywords: MOLECULAR CALCULATIONS; HYDROGEN STORAGE; BASIS-SETS; C-C; B-N; BORON; DECOMPOSITION; BOND; ROUTE; PHASE